Gestión y desarrollo de las RR.PP ante el know how universitario de las marcas académicas - Almeida Hidrovo, Karla Fernanda (2020)
The present investigative process has as its starting point, the management and strategy that is handled from the institutional order, seeking to characterize the importance of the strategic management that accompanies institutions or organizations based on their organizational and communicational structure, the same that evokes in the development and projection of the Know-How of its processes and the constant interaction of its audiences as well as the acceptance and projection of its activities in favor of the entity, which in this case for the purposes of this research is the management and development of the Vicente Rocafuerte de Guayaquil Lay University (ULVR) . The methodology is of a dual nature, the methodological collection techniques were direct observation, interviewing experts and the survey technique applied to a significant percentage of the University period 2019- b, as a result, the considerations and specifications that are made through its planning are sought Organizational ion and its projection through implementation and strategic management………..